Precarious Coexistence in Maluku: Fear and Trauma in Post-Conflict Christian-Muslim Relations - Riyanto, Geger (Muslim Politics Review, 2023)
This paper examines the precarious coexistence between Muslims and Christians in post- conflict Maluku, Indonesia. The lasting effects of brutal conflict have left fear and trauma as the dominant emotions in the relationships of local residents. While these emotions are commonly seen as hindrances to peace by scholars and non-scholars alike, in post-conflict societies, they are inescapable and deeply ingrained. Nevertheless, they not only drive division, but also the desire to maintain peace. In Maluku, both Christians and Muslims are bound by the shared understanding that their current peaceful coexistence is delicate, and they must be cautious in their interactions with people of different religions, despite ongoing animosity and mistrust. This ongoing reality in Maluku calls for a reassessment of the normative tendency in peace discourses, which expect peace to be either ideal or impaired and tend not to be contextual in evaluating peace. To understand post-conflict coexistence better, we need to comprehend how emotions towards other groups operate in the emerging social settings.